THE INFLUENCE OF DIGITAL MEDIA ON READING AND WRITING PRACTICES - Jumabayeva Mahzunabonu; Abdurahmonov To'raxon (TADQIQOTLAR.UZ, 2024)
In the digital age, media has revolutionized the way people access information, communicate, and express themselves. The rapid development of digital media, including smartphones, tablets, e-books, and social platforms, has had a profound impact on reading and writing practices. This article explores how digital media shapes literacy habits, challenges traditional practices, and offers new opportunities for both reading and writing.